1991
DOI: 10.1111/j.1365-2249.1991.tb05592.x
|View full text |Cite
|
Sign up to set email alerts
|

Triggered human mucosal T cells release tumour necrosis factor-alpha and interferon-gamma which kill human colonic epithelial cells

Abstract: SUMMARYTcell activation can lead to local tissueinjury in organ culture studies of human fetal jejunum, either directly throughcytotoxicity or indirectly by the release of cytotoxic cytokines. The goal of this study was to establish in vitro whether cyiotoxic cytokines can be released by isolated colonic T cells and what cytokine interactions are required for killing of human colonic epithelial cells. Cytokinecontaining supernatants were induced by incubating un.separated lamina propria tymphocyies (LPL) or mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…This cytokine is most likely a major factor in the increased epithelial expression of secretory component (polymeric Ig receptor; pIgR) and HLA-DR seen in the flat lesion [23]. Especially together with tumour necrosis factor (TNF)-␣ [24], IFN-␥ may also contribute to increased epithelial permeability [25] and expansion of mucosal plasma cells (PCs) as discussed later. An additional feature of active humoral immunity is constituted by subepithelial complement deposition, which may represent an early innate pathogenic insult on the mucosa [26].…”
Section: Induction and Effect Of Mucosal Cytokinesmentioning
confidence: 97%
“…This cytokine is most likely a major factor in the increased epithelial expression of secretory component (polymeric Ig receptor; pIgR) and HLA-DR seen in the flat lesion [23]. Especially together with tumour necrosis factor (TNF)-␣ [24], IFN-␥ may also contribute to increased epithelial permeability [25] and expansion of mucosal plasma cells (PCs) as discussed later. An additional feature of active humoral immunity is constituted by subepithelial complement deposition, which may represent an early innate pathogenic insult on the mucosa [26].…”
Section: Induction and Effect Of Mucosal Cytokinesmentioning
confidence: 97%
“…We then showed that IL-10 depletion led to an inflammatory response, monitored by the expression of TNF-α and IFN-γ. We chose these Th1-type cytokines because (a) both are part of the mucosal immune response in the spontaneous colitis in IL-10 -/-mice (5); (b) TNF-α is a major cytokine involved in the perpetuation of inflammation during inflammatory bowel diseases (32-34); and (c) both are known to induce epithelial barrier disruption either independently or in combination (30,(35)(36)(37)(38)(39)(40)(41). We found a modest increase in TNF-α mRNA and protein levels in IL-10-depleted mucosa explant cultures at 48 h, in line with the partial downregulation of BCL3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Production of TNFα by circulating neutrophils was higher in IBD patients compared to controls (11) and there is evidence of increased mucosal TNFα production in CD patients (12). This cytokine is probably responsible for tissue damage due to its ability to kill colonic epithelial cells (13), as well as for causing epithelial barrier disruption (14). The production of IL-10 and TNFα presents important interindividual variations, with high hereditability regulated by gene polymorphisms at their promoter regions.…”
Section: Introductionmentioning
confidence: 97%